Diffuse gallbladder wall thickening in autoimmune hepatitis: An unusual presentation - Chitchai Rattananukrom (2022)
A 63-year-old woman presented with jaundice and epigastric pain for 2 weeks. Physical examination revealed marked jaundice, and palpable gallbladder with right upper quadrant tenderness. Liver function test was remarkable for hepatocellular injury pattern. Antinuclear antibody and anti-smooth muscle antibody were positive with high titre and serum IgG was elevated more than upper normal range. Ultrasound and CT scan demonstrated mildly diffuse periportal oedema of liver parenchyma and markedly diffuse gallbladder wall thickening up to 2 cm. Liver histology showed focal interface hepatitis with prominent plasma cell infiltration and cluster formation, moderate lobular spotty necrosis and emperipolesis consistent with autoimmune hepatitis. The patient was treated with steroid and azathioprine. She had complete resolution of symptoms and normal biochemical laboratory results. Diffuse gallbladder thickening was seen in acute hepatitis from definite autoimmune hepatitis.